2001
DOI: 10.1200/jco.2001.19.19.3944
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening for Hereditary Nonpolyposis Colorectal Cancer: A Prospective, Population-Based Study

Abstract: We conclude that the incidence of molecularly confirmed HNPCC (one [0.3%] of 336) in a high-incidence area for CRC is lower than in previous biomolecular and clinical estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 28 publications
7
44
0
1
Order By: Relevance
“…The frequency of defective protein expression of hMSH2 and/or hMLH1 in cases with CRC alone was 7.2% in our study and this finding closely correlated to the reported frequency of MSI or RER in sporadic CRC. MSI-H has been reported to be observed from 5-20% of sporadic CRC cases (27,28). A high frequency loss of the two MMR gene proteins was observed in patients with GC and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of defective protein expression of hMSH2 and/or hMLH1 in cases with CRC alone was 7.2% in our study and this finding closely correlated to the reported frequency of MSI or RER in sporadic CRC. MSI-H has been reported to be observed from 5-20% of sporadic CRC cases (27,28). A high frequency loss of the two MMR gene proteins was observed in patients with GC and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15% of all colorectal cancers show high-level microsatellite instability (MSI) (Aaltonen et al, 1993;Ionov et al, 1993;Thibodeau et al, 1993) reflecting dysfunction of the postreplicative DNA mismatch repair system, and in most of these tumors (roughly 10% of all colon cancers), the instability stems from CpG methylation-mediated silencing of the mismatch repair gene hMLH1 (Kane et al, 1997). Indeed, hMLH1 promoter methylation is a defining feature of CIMP-positive colorectal cancers, which are preferentially located in the right colon and usually affect older women (Malkhosyan et al, 2000;Percesepe et al, 2001;Slattery et al, 2001). An even larger percentage of colorectal cancers (20-40%) are characterized by promoter methylation-mediated silencing of MGMT (Esteller et al, 2000;Whitehall et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The most common inherited condition that gives rise to MSI positive cancers is Lynch syndrome, an autosomal dominant disease, also referred to as Hereditary Non-polyposis Colorectal Cancer (HNPCC), where gastric cancer is a common neoplasia, occurring in 6% of Lynch syndrome cases (Percesepe et al, 2001;Samowitz et al, 2001). Predisposed individuals carry a recessive, first-hit germline mutation in the MMR genes, including large genomic rearrangement, which account for 5-20% of all mutations.…”
Section: Mutational Impairment Of Mmr Activity and Pathogenic Signifimentioning
confidence: 99%